2009
DOI: 10.1371/journal.pone.0006570
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Microbial Fuel Cell Arrays Reveal Electrochemically Active Microbes

Abstract: Microbial fuel cells (MFCs) are remarkable “green energy” devices that exploit microbes to generate electricity from organic compounds. MFC devices currently being used and studied do not generate sufficient power to support widespread and cost-effective applications. Hence, research has focused on strategies to enhance the power output of the MFC devices, including exploring more electrochemically active microbes to expand the few already known electricigen families. However, most of the MFC devices are not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 43 publications
4
98
1
Order By: Relevance
“…), Firmicutes (Bacillus sp., Lysinibacillus sp.) and Actinobacteria (Leucobacter chironomi; Rhodococcus sp [14,56]. However, we were unable to identify any metal reducing bacteria from our sample.…”
Section: Isolation Of Bacteria From Potomac River Sedimentmentioning
confidence: 72%
“…), Firmicutes (Bacillus sp., Lysinibacillus sp.) and Actinobacteria (Leucobacter chironomi; Rhodococcus sp [14,56]. However, we were unable to identify any metal reducing bacteria from our sample.…”
Section: Isolation Of Bacteria From Potomac River Sedimentmentioning
confidence: 72%
“…While earlier studies demonstrated principles, sufficiently efficient bacterial species have yet to be discovered. A new microbial fuel cell array has been reported for the discovery of electrochemically active microbes, to compare species and strains for selection and practical use [28]. The array consists of 24 integrated chambers, each containing an anode and a cathode, and allows separate examinations of 24 miniature samples to quantitate and compare microbial power outputs.…”
Section: Unmodified Electrochemical Array Elementsmentioning
confidence: 99%
“…These advantages due to the microscale of the MFC allow developing highthroughput screening devices to study the current limits and future potential of MFCs. As a result, optimization of MFCs can be done by screening for microorganisms with higher electricity generation capabilities or by studying the influence of electrode materials and structures on electricity generation [Hou et al 2009;Qian et al 2009;Wang et al 2011b].…”
Section: Microbial Fuel Cells : Microbial Production Of Electricitymentioning
confidence: 99%